Studi Kasus Penerapan PSAK 23 dalam Pengakuan Pendapatan pada PT G - Wahyu Vitaningsih, Tri Ariani; Budiwibowo, Satrijo; Astuti, Elly (E-Jurnal Akuntansi, 2020)
The study was conducted to determine the application of PSAK 23 2018 Revision in recognition of income at PT G. This type of research is a qualitative case study research. Data collection was carried out by documenting the results of interviews from social media, related business news, the revised PSAK 2018 and the applicable laws and regulations. Data analysis was performed by comparing PSAK, Corporate Financial Reports and Business News related to the case of PT.G. The results showed that PT G's financial statements have not fully complied with regulations related to the preparation of financial statements. The factor causing the discrepancy is the existence of a conflict of interest in the management of PT G. Keywords: PSAK 23; Revenue Recognition; Adequacy Of Accounting Regulations; Conflict Of Interest.